Writing systems: political and bibliological issues - Migoń, Krzysztof (Knygotyra, 2024)
Bibliology — the study of the book’s culture—is rich in the tradition of writing research. The theoretical basis of this paper is the scheme of bibliology by Robert Estivals, who proposed a new course of this science called "the political research of writing: the authorities and the writing systems." Writing systems have always been understood as tools of social communication, which were highly influenced by politics. For political reasons, writing creates a certain (sometimes an entirely new) type of media reality. The mutual relationships that shape this process occur in the following sequence: politics → writing (a writing system) → book (a book system) → user of the book system. The following spheres are of primary significance: (1) The creation of scripts for languages and ethnic groups whose languages are unwritten; (2) The alterations of writing systems introduced by state, religious authorities, and/or intellectual elites; (3) The quantity of writings used in one language; (4) The great number of writings used in one state; (5) Writing as the means of upholding national and religious heritage; (6) The national and local variants of "universal" writings as a form of political manifestation. A political perspective is an all-too-useful scientific category as far as the study of writing systems and books within bibliology is concerned. Its application enriches our knowledge of the culture of the book from global and national (ethnic) perspectives. It may also play an important role in contemporary book policy on a local or international scale.